Al-KHITAB AL-WATHANI FI QASAIDI AHMAD SYAUQI - Alfatawi, Ahmad Talkhis; Masyhud, Fathin (Journal of Arabic Literature (JaLi), 2022)
Ahmad Syauqi is a well-known Egyptian poet. He also earned the nickname amīr al-syu'arā' (poet prince) from Middle Eastern poets. When World War 1 and 2 broke out, Syauqi loudly voiced nationalism in his poems, even he was exiled to Andalus (Spain) by the British who then colonized Egypt. Therefore, this research will discuss the various expressions of nationalism ala Ahmad Syauqi in his poetry. This research is a descriptive qualitative research using content analysis. The data obtained in this study were taken from several collections of Ahmad Syauqi's poetry and poetry, especially nationalism, which were then analyzed descriptively. The results of the research can be concluded that the various expressions of nationalism ala Ahmad Syauqi in his poetry are divided into poetry of love for the country, resistance and praise to other nations. Thus, it is clear that Ahmad Syauqi is a nationalist poet, many of his poems talk about his homeland, namely Egypt and everything in it, the unity of the Arabs, against all forms of colonialism, and praising other nations he once visited, especially in the Middle East region.